PEMANFAATAN HASIL EVALUASI DAN REFLEKSI DALAM PEMBELAJARAN DESAIN GRAFIS PERCETAKAN DI SMKN 3 CIMAHI - Albari, Fardan Barkah; Augustianingrum, Nurul Khofifah; Rachmawati, Wineu Siti (Eduscience : Jurnal Ilmu Pendidikan, 2021)
Learning evaluation is an important thing that must be considered by a teacher. This research was for find out how learning evaluation was carried out at SMKN 3 Cimahi and a form of reflection on the learning evaluation that had been implemented. This research was conducted using qualitative methods with interviews. From the research conducted by SMKN 3 Cimahi, evaluating learning by dividing the assessment into 2 types, that is theory and practice with a large of 30% for theory and 70% for practice. The implementation of learning reflection in SMKN 3 Cimahi applies additional material that is useful for the next subject because the learning objectives have been achieved. Keywords: Evaluation of Study, Vocational High School, Reflection of Learning